Analysis of the Impact of Increasing Tourist Visits on Economic Growth in Palabuhanratu Sukabumi Tourism Destinations - Setiono, Agus; Baso, Andi Sabirin; Sasmito, Priyo; Nurhajra, Andini (West Science Journal Economic and Entrepreneurship, 2023)
In Palabuhanratu, Sukabumi, this study aims to examine the effects of rising tourist numbers on economic development. A poll of 100 respondents, including local communities, traders, and tourist entrepreneurs, was employed as the study methodology. Descriptive analysis and basic linear regression were both used to analyze the given data. The findings demonstrated that tourism has a considerable beneficial influence on economic development in the Palabuhanratu, Sukabumi destination. The study also found that natural and cultural attractions, quality of service, and ease of accessibility are important factors in increasing the number of tourist visits.